Alzheimer's disease qEEG: spectral analysis versus coherence. which is the best measurement? - Renato Anghinah; Paulo Afonso Medeiros Kanda; Helder Frederico Lopes; Luis Fernando Hindi Basile; Sérgio Machado; Pedro Ribeiro; Bruna Velasques; Koichi Sameshima; Daniel Yasumasa Takahashi; Lécio Figueira Pinto; Paulo Caramelli; Ricardo Nitrini (Arquivos de Neuro-Psiquiatria)
There is evidence in electroencephalography that alpha, theta and delta band oscillations reflect cognitive and memory performances and that quantitative techniques can improve the electroencephalogram (EEG) sensitivity. This paper presents the results of comparative analysis of qEEG variables as reliable markers for Alzheimer's disease (AD). We compared the sensitivity and specificity between spectral analysis (spectA) and coherence (Coh) within the same group of AD patients. SpectA and Coh were calculated from EEGs of 40 patients with mild to moderate AD and 40 healthy elderly controls. The peak of spectA was smaller in the AD group than in controls. AD group showed predominance of slow spectA in theta and delta bands and a significant reduction of inter-hemispheric Coh for occipital alpha 2 and beta 1 and for frontal delta sub-band. ROC curve supported that alpha band spectA was more sensitive than coherence to differentiate controls from AD.